Peran Serta Masyarakat dan Kewenangan Kelembagaan Pengelolaan Lingkungan Hidup Berbasis Pariwisata Berdasarkan Tinjauan Yuridis - Zakaria, Iwan Acuan (Program Studi Hukum Universitas Pendidikan Muhammadiyah Sorong, 2022)
The purpose of this research is to find out the importance of environmental management and also tourism through the participation of the government and also the community from a juridical perspective, bearing in mind that Indonesia is a country full of natural resources. This research is a descriptive study of research procedures, namely the description stage of various literature using normative legal science research methods. It’s necessary to note that the environment plays a very important role in people's lives, where every community certainly needs a clean environment and is far from pollution, including those caused by environmental management and tourism that have not fulfilled the provisions in accordance with the governing law, therefore the role as well as the government and society in protecting and managing the environment and tourism is very important, as a form of prioritizing legal certainty and legal benefits. In the context of this management, every community is given the right to exploit its resources in the field of tourism business based on the provisions of the governing law.